Veterinary-Sanitary Inspection in the System of Control Measures Against Trichinellosis - A. V. Uspenskiy; F. K. Skvortsova (Российский паразитологический журнал, 2020)
The purpose of the research is a comprehensive evaluation of existing methods and devices for veterinary-sanitary inspection on trichinellosis.Materials and methods. In the course of researches diagnostic and processing characteristics of existing tools and methods for trichinelloscopic control were determined using specimens of muscular tissue from experimentally infected laboratory animals.Results and discussion. It has been established that the major methods for inspection in the case of trichinellosis are compressor trichinelloscopy and peptolysis method (digestion of muscular tissue in simulated gastric fluid). Devices permitting to use them in different technological conditions were created for the realization of each of these diagnostics methods. Thus, devices of TP-type for the field work researches on trichinellosis based on appliance of optical system of control were recommended for compressor trichinelloscopy. Complex of devices of AVT-type permitting to study large lots of meat by-products and waste was developed for inspection of carcasses and meat products under manufacturing conditions.